House price cycles, housing systems, and growth models - Karsten Kohler; Benjamin Tippet; Engelbert Stockhammer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
The paper provides a framework for theorising the role of house price cycles in national growth models. We synthesise Minskyan approaches with comparative political economy (CPE) by arguing that institutions influence the extent to which countries experience what we call 'house-price-driven growth models'. First, we argue that house price dynamics have been undertheorised in existing growth models analysis. Finance-led models can be properly understood only against the background of rising house prices that stimulate consumption through wealth effects and investment through construction. Second, we identify behavioural and Minskyan theories of housing cycles as suitable frameworks to theorise the impact of housing on growth. However, this literature does not provide an analysis of cross-country differences in housing cycles. Third, drawing on the CPE literature on housing systems, we argue that factors such as private homeownership and mortgage-credit encouraging institutions can explain differences in the intensity of housing cycles. We provide preliminary empirical support for this framework from a cross-country analysis. Our results show strong cross-country heterogeneity in the intensity of housing cycles. Countries with more intense house price cycles also tend to exhibit more volatile business and debt cycles. Homeownership rates and mortgage-credit encouraging institutions are positively correlated with the volatility of house price cycles.
Keywords: E32; O57; R21; R31; B52; 330; post-Keynesian economics; comparative political economy; growth models; housing; house price cycles